PUTUSNYA PERKAWINAN AKIBAT SUAMI MENIKAH TANPA IZIN DARI ISTRI - Suhaila Zulkifli (Universitas Islam Sumatera Utara, 2019)
Marriage is one of the Sunnahtullah that applies to all creatures created by Allah SWT, including humans, animals and plants. Marriage is defined as an agreement between men and women. Many families experience destruction because each individual runs without a clear guideline, as contained in Islamic teachings about marriage. Divorce is essentially a process in which the relationship between husband and wife does not meet harmony in marriage anymore. Regarding the definition of divorce, the marriage law does not regulate explicitly, but only determines that divorce is only one reason for the breakup of marriage besides other causes, namely death and court decisions. In this study, the author's team discussed a problem regarding the termination of marriage caused by a husband who is married without his wife's permission. The research is a normative juridical study using legislation review approach, and this study also applies primary, secondary and tertiary legal materials. The writing technique made by the writing team is descriptive analytical by which the obtained data is then arranged systematically to be subsequently analyzed to reach a conclusion. Keywords: marriage, polygamy, divorce